Structural basis of long-range transcription–translation coupling - Chengyuan Wang; Vadim Molodtsov; Shashank Shandilya; Linlin You; Jing Zhang; Konstantin Kuznedelov; Bryce E. Nickels; Jason T. Kaelber; Gregor Blaha; Richard H. Ebright (Proceedings of the National Academy of Sciences, 2026)
Structures recently have been reported of molecular assemblies that mediate transcription–translation coupling in Escherichia coli . In these molecular assemblies, termed “coupled transcription–translation complexes” or “TTC-B,” RNA polymerase (RNAP) directly interacts with the ribosome, the transcription elongation factor NusG or its paralog RfaH forms a bridge between RNAP and ribosome, and the transcription elongation factor NusA optionally forms a second bridge between RNAP and ribosome. Here, we report structures of coupled transcription–translation complexes having mRNA spacers between RNAP and ribosome longer than the maximum-length mRNA spacer compatible with formation of TTC-B. The results define a class of coupled transcription–translation complex, termed “TTC-LC,” where “LC” denotes “long-range coupling.” TTC-LC differs from TTC-B by a ~60° rotation and ~70 Å translation of RNAP relative to ribosome, resulting in loss of direct interactions between RNAP and ribosome and creation of a ~70 Å gap between RNAP and ribosome. TTC-LC accommodates long mRNA spacers by looping out mRNA from the gap between RNAP and ribosome. We present evidence that TTC-LC is a functional intermediate in assembling and disassembling TTC-B, mediating pre-TTC-B transcription–translation coupling before a ribosome catches up to RNAP, and mediating post-TTC-B transcription–translation coupling after a ribosome stops moving and RNAP continues moving. We show that TTC-B, but not TTC-LC, is severely defective in RNA-hairpin-dependent transcription termination, and that both TTC-B and TTC-LC are severely defective in Rho-dependent transcription termination.